2019
DOI: 10.1192/bjo.2019.88
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of patients, carers and mental health staff on early warning signs of relapse in psychosis: a qualitative investigation

Abstract: on behalf of the EMPOWER Research Group* Background Relapse prevention strategies based on monitoring of early warning signs (EWS) are advocated for the management of psychosis. However, there has been a lack of research exploring how staff, carers and patients make sense of the utility of EWS, or how these are implemented in context. AimsTo develop a multiperspective theory of how EWS are understood and used, which is grounded in the experiences of mental health staff, carers and patients. MethodTwenty-five f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Concern centered on fears of clinicians and services responding to changes in clinical states in unwanted ways, such as changes to medications when reporting low mood. This has been reported in other studies [ 29 , 30 ], reflecting the importance of considering the role of, and response to, personal clinical information collected in daily life from users of clinical services.…”
Section: Discussionsupporting
confidence: 64%
“…Concern centered on fears of clinicians and services responding to changes in clinical states in unwanted ways, such as changes to medications when reporting low mood. This has been reported in other studies [ 29 , 30 ], reflecting the importance of considering the role of, and response to, personal clinical information collected in daily life from users of clinical services.…”
Section: Discussionsupporting
confidence: 64%
“…Similar to previous findings, participants’ accounts showed that decision-making was influenced by broader contextual factors (Allan et al, 2020), including high caseloads, perceived expectations from society and accountability with risk management a priority. Concerns about blame were raised, in accordance with previous research (Henderson et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…The use of digital technology in the treatment, management, and support of psychotic disorders has been an area of interest to the digital mental health field for some time (Allan et al., 2020; 2018, 2019; Bell et al., 2018; Bradstreet, Allan, & Gumley, 2019; Lal, Nguyen, & Theriault, 2018; Lim et al., 2019). Due to the early age of onset and symptom severity, psychotic disorders can significantly impact a person’s psychological and functional life trajectory (Bucci et al., 2018).…”
Section: Introductionmentioning
confidence: 99%